2020
DOI: 10.7150/jca.35810
|View full text |Cite
|
Sign up to set email alerts
|

Cell Block as a Surrogate for Programmed Death-Ligand 1 Staining Testing in Patients of Non-Small Cell Lung Cancer

Abstract: Introduction: Programmed death-ligand 1 (PD-L1) staining is used in clinical practice to guide the proper use of immune checkpoint inhibitors. This study aimed to investigate the accuracy of PD-L1 staining of non-small cell lung cancer (NSCLC) cytological cell block samples. Methods: Paired cytological cell block and surgical resection samples were consecutively collected from January 2016 to February 2017 in Shanghai Pulmonary Hospital, Tongji University. Two trial-validated PD-L1 assays (28-8 and SP142) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In studies with cytology fixed in formalin, that is, excluding studies with nonformalin or mixed formalin/nonformalin fixation, the concordance with paired histological specimens was 81–82% (333–336/410 cases) at cutoff 1% and 88–89% (316–317/358 cases) at cutoff 50% based on 7 studies [38, 39, 48, 50, 58, 60, 62]. If instead, only including studies with cytology fixed in nonformalin fixatives, excluding mixed formalin/nonformalin fixation, the concordance with paired histological specimens was 79–81% (500–512/633 cases) at cutoff 1% and 88–89% (554–565/633 cases) at cutoff 50% based on 9 studies including the Lund cohort from the present study [41, 45, 46, 49, 52, 55, 56, 62].…”
Section: Resultsmentioning
confidence: 75%
“…In studies with cytology fixed in formalin, that is, excluding studies with nonformalin or mixed formalin/nonformalin fixation, the concordance with paired histological specimens was 81–82% (333–336/410 cases) at cutoff 1% and 88–89% (316–317/358 cases) at cutoff 50% based on 7 studies [38, 39, 48, 50, 58, 60, 62]. If instead, only including studies with cytology fixed in nonformalin fixatives, excluding mixed formalin/nonformalin fixation, the concordance with paired histological specimens was 79–81% (500–512/633 cases) at cutoff 1% and 88–89% (554–565/633 cases) at cutoff 50% based on 9 studies including the Lund cohort from the present study [41, 45, 46, 49, 52, 55, 56, 62].…”
Section: Resultsmentioning
confidence: 75%
“…to the cellularity of the cytology specimens. 61 In this study, the authors demonstrated that the concordance rate at a cut-off of 50% was near perfect (>0.80) for cell count of 400 for clone 28-8 and cell count of 500 for clone SP142 compared to moderate concordance at cellularity between 100 and 500 cells.…”
Section: Studies Have Shown That Concordance Rates Vary In Direct Pro...mentioning
confidence: 62%
“…Torous et al observed a similar distribution of cases, with no significant differences of cases with high PD‐L1 expression between cell blocks (35.1%) and surgical pathology group (34.8%, consisting of biopsies and surgical specimens) 18 . Dong detected lower values with the PD‐L1 28‐8 assay, with high PD‐L1 positivity in 20.5% of cell blocks and 27.7% of surgical specimens 19 . Vigliar et al observed fewer cases with high expression of PD‐L1 in cell blocks (4.9%) in comparison to biopsies (28.7%) and surgical specimens (15.7%) 20 ; however, cell blocks represented a limited number of their study (41 cell blocks).…”
Section: Discussionmentioning
confidence: 78%